ON THE SPAWNING ACTIVITIES OF KINGFISH, SCOMBEROMOROUS COMMERSON, IN OMAN WATERS - THANGARAJA, M.; AL AISRY, AHMED (Journal of Indian Fisheries Association, 2016)
The spawning activities of kingfish, Scomberomorus commerson, in Omanwaters are traced out for the first time. The possible spawning period andspawning ground are identified on the basis of collection of its eggs andlarvae from Oman waters. The eggs and early larval characteristics aredescribed suitably with photographic illustration of 4.9 - mm larva. Theoptimum surface water temperature and salinity recorded for the occurrenceof kingfish eggs and larvae are 23.57 - 26.05 oC and 36.0 - 36.1 %o, respectively.Keywords.: King fish, spawning grounds, Development.